Creación de una línea de productos rellenos de sábila - Rivera Morales, Thalia Roxana (2018)
The project started after an investigation, a formulation, and experimentation that helped to create a some product with aloe vera stuffing. At first, information about aloe vera was compiled from many sources that are trusted and full of information. These sources support the knowledge that aloe vera has a lot of benefits for people’s health due to its properties. In the same way, supplier were searched and met in Quito, same that follow the Project guidance. Also, recipes for four, world know products were formulated, allowing to test and include the aloe vera stuffing. Second, the chocolate products filled with aloe vera were validated working with the focus group method and expert validation method, there is where improvements in the recipes were made, resulting in a better flavor, texture and appearance of the final products. Finally, a manual was made, in which the correct process behind each product can be seen. As a conclusion it can be said that, the project assures the user to get product fill with aloe vera, using healthy ingredients that are sanitary and quality guaranteed. Also, it shows the process the brand, register and label that let the product to be marketed.